Multicultural Values Representation in the English Textbook â€œEnglish in Mindâ€ for Junior High School - Rifdatul Habibah; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims to look into the multicultural values represented in the Merdeka Curriculum textbook for Junior High School, "English in Mind." The research employed a qualitative method to acquire specific information regarding multicultural ideals and English textbook data. This content analysis study examined multicultural values using Barthes' four multicultural elements. The research revealed findings indicating that all aspects of multicultural values are included in this EFL textbook. Appreciating Other People's Perspectives is mainly covered in this textbook. The textbook only discusses the multicultural value component, which represents the duty of the world community. ELT specialists and English teachers worldwide have welcomed this new paradigm, which theorizes the integration of regional English variations and multicultural elements to improve intercultural communicative skills. The examined textbook expresses a multicultural viewpoint by accepting and valuing the world's varied customs. Regarding the result of this research, further research is undertaken to identify the approaches, strategies, and procedures for teaching multicultural values to students of varying ages.